Presentations for Navigating Sudan’s Conflict: Research Insights and Policy Implications - Siddig, Khalid; Abushama, Hala; Intini, Vito; Svensson, Fredrik; Kirui, Oliver K.; Chaitani, Youssef; Mwiinga, Billy; Siambi, Moses; Ahmed, Mosab O. M. (2024)
The conflict in Sudan has persisted since April 2023, with the violence intensifying in December 2023. As of February 2024, the crisis has displaced more than 8.1 million people internally, with an additional 1.7 million seeking refuge across borders. As of mid-April, ACLED has reported about 13,900 fatalities across Sudan, and the Sudan Federal Ministry of Health reports that around 27,700 people were injured between 15 April 2023 and 26 January 2024. The violence has spread into parts of central and eastern Sudan that were initially considered safe havens, resulting in more displacement, and further increasing pressure on states in eastern Sudan.